Spherical Layout Implementation using Centroidal Voronoi Tessellations - Larrea, Martin; Urribarri, Dana; Martig, Sergio; Castro, Silvia (Journal of Computing, 2009)
The 3D tree visualization faces multiple challenges: the election of an appropriate layout, the use of the interactions that make the data exploration easier and a metaphor that helps in the process of information understanding. A good combination of these elements will result in a visualization that effectively conveys the key features of a complex structure or system to a wide range of users and permits the analytical reasoning process. In previous works we presented the Spherical Layout, a technique for 3D tree visualization that provides an excellent base to achieve those key features. The layout was implemented using the TriSphere algorithm, a method that discretized the spheres's surfaces with triangles to achieve a uniform distribution of the nodes. The goal of this work was centered in a new algorithm for the implementation of the Spherical layout; we called it the Weighted Spherical Centroidal Voronoi Tessellations (WSCVT). In this paper we present a detailed description of this new implementation and a comparison with the TriSphere algorithm.